Redescription of the tadpole of Leptodactylus flavopictus Lutz, 1926 (Anura: Leptodactylidae) from Pilar do Sul, São Paulo, Brazil - Martins, Renato Augusto; Becker, C. Guilherme; Haddad, Célio Fernando Baptista; Pendu, Yvonnick Le; Solé, Mirco; Mira-Mendes, Caio Vinicius De (Zootaxa, 2020)
Frogs of the subfamily Leptodactylinae Werner can be found from southern Texas (USA) to southern Brazil, including the northern Antilles (Frost 2019). This subfamily is composed of 98 recognized species and the genus Leptodactylus Fitzinger contains the largest number of species (74 sp.) (Frost 2019). A study conducted by de Sá et al. (2014) provided a phylogeny of Leptodactylus based on molecular analysis, adult and larval morphology, and behavioral data. Currently, four species groups are recognized within this genus: L. fuscus group, L. pentadactylus group, L. latrans group, and L. melanonotus group (de Sá et al. 2014).